The Effect of Working Capital Management on Profitability of Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange - Maya, Azaria; Rahmi, Anindiva; Setiawan, Donny; Lestari, Henny (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The manufacturing sector, notably the food and beverage industry, plays a pivotal role in Indonesia's economy, contributing 37.77% to the GDP in Q1 2022. This study delves into the working capital management of food and beverage manufacturing companies listed on the Indonesia Stock Exchange. With a focus on the cash conversion cycle (CCC), the research evaluates profitability using operating profit margin (OPM) and return on equity (ROE). The sector has exhibited positive international trade, with food and beverage exports reaching USD 10.92 billion and imports at USD 3.92 billion during the same period. To sustain and improve industry performance, companies must develop robust capabilities for profitability, emphasizing the efficient management of financial resources such as cash, receivables, inventory, and payables. The study provides valuable insights for companies, highlighting the significance of OPM and ROE in evaluating working capital and influencing overall profitability.